Prevalence and Risk Factors for Amputations in Patients with Diabetic Foot - Alcántara Pío, Wilder (1999)
OBJECTIVE: To determine the prevalence and risk factors associated to diabetes-related lower limb amputations. MATERIAL AND METHODS: A descriptive, retrospective, longitudinal study, assessing the foots’ survival among 206 inpatients with diabetic foot at Hospital Nacional Dos de Mayo, between 1989 and 1997. RESULTS: Mean age was 61,4 years (range 27-86). Most of patients had tipe II diabetes mellitus (96,21%). Wagner’s classification of diabetic foot lesions was used to stratify the cases. Grades II - III in 35,92% and IV - V in 64,08% of patients were seen. 126 patients underwent amputation (61,16%), and 13 a reamputation (10%) of the lower limb. The main risk factors related to amputations were neuropathies (85,71%) and vasculopathy (71,43%). Mean age of amputation was 65,8 years. Two-months accumulated foot survival rate was 29% and amputation rate was 4%; whereas these were 16% and 25%, respectively at 13 months. CONCLUSIONS: Prevalence of amputations among diabetic foot inpatients was 61%. The main risk factors were neuropathies and vasculopathies. Amputation risk doesn’t decrease with a longer hospital length of stay.